Pengaruh Inovasi Iklan, Hubungan Masyarakat, dan Promosi terhadap Loyalitas dan Keputusan Pembelian Konsumen: Studi Produk On Line di Indonesia (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Nowadays, products marketed online have become concerned  for the public along with the advancement of information technology innovation. Various types of products from various companies are known through innovative marketing. This study aims to determine the differences in loyalty and purchasing power of online products between men and women as well as to investigate how advertising, public relations (PR), and direct promotion innovation affect consumer loyalty and purchasing decisions for online products in Indonesia. Using a sample of 60 respondents, primary data was collected through a 5-likert scale questionnaire both through e-form and face-to-face distribution. SPSS analysis resulted in no significant difference between men and women in consumer loyalty and purchasing decisions. The results of the study also showed that advertising and promotional innovation directly to the target market significantly and positively influenced the increase in consumer loyalty and purchasing decisions. However, public relations innovation did not affect consumer loyalty and purchasing decisions.